Adaptive regulation strategy of the soft deformable actuator based on angle self-sensing. Issue 1 (1st December 2022) - Yao, Haiying; Wen, Yintang; Zhou, Zixiang; Tian, Hongmiao; Zhang, Yuyan; Luo, Xiaoyuan
Abstract: Soft robots can adapt to various unstructured environments and have received extensive attention. The integrated structure of sensing and actuation makes soft robots more miniaturized and integrated, enriching their usage scenarios. The multiple degrees of freedom of soft actuators facilitate flexible deformation but also bring challenges to precisely control the deformation. This work presents a novel Liquid Crystal Elastomer-based soft actuator with self-sensing. The kinetic model of a soft finger structure made of the above soft actuator is proposed to facilitate the controller design. Considering the non-predetermined external excitation, a deformation regulation strategy based on a sliding mode controller is designed. Under the action of the controller, the bending angle of the finger joint can be stabilized in a smaller range around the desired value based on the feedback of the self-sensing information. This research realizes the integration of sensing, actuation, and control, enabling the flexible structure can organically adapt to the environmental dynamics and uncertainty in nature, which cannot be achieved by the existing flexible structure deformation control.